2020
DOI: 10.1016/j.atmosenv.2020.117731
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of secondhand cannabis smoke from common smoking methods: Calibration factor, emission rate, and particle removal rate

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…This finding was consistent with previous studies testing the decay rates of 4 different marijuana sources (joint, glass pipe, water pipe, and vaping pen) inside a car chamber (Zhao et al, 2020) and in a residential bedroom . Li et al (2020) found PM 2.5 particle loss rates for vaping aerosols (from e-cigarettes in this case) were >4 times as high as that for -Di-Ethyl-Hexyl-Sebacat (DEHS) aerosols with little evaporation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This finding was consistent with previous studies testing the decay rates of 4 different marijuana sources (joint, glass pipe, water pipe, and vaping pen) inside a car chamber (Zhao et al, 2020) and in a residential bedroom . Li et al (2020) found PM 2.5 particle loss rates for vaping aerosols (from e-cigarettes in this case) were >4 times as high as that for -Di-Ethyl-Hexyl-Sebacat (DEHS) aerosols with little evaporation.…”
Section: Resultssupporting
confidence: 92%
“…To accurately represent the actual PM 2.5 concentration, the calibration factor (CF) -the ratio of gravimetrically-to-optically-measured 9 PM 2.5 concentration is needed for each source type (e.g., Jiang et al, 2011;Dacunto et al, 2013). In a previously published paper, we determined the CFs for the two marijuana source types: 0.35 for joint smoking and 0.44 for vaping (Zhao et al, 2020) for the reference SidePak monitor; they were applied along with the inter-monitor slopes to rescale all PM 2.5 measurement in this study (e.g., actual concentration for vaping = direct reading of SidePak i × (0.44/[slope of SidePak] i ) where i = 1-5). Jiang et al (2011) found that CFs for SidePak monitors remained relatively constant over time; for a 16-month period, the average difference was ~3%.…”
Section: Sources and Protocolmentioning
confidence: 99%
“…They are, therefore, solid at room temperature (melting point >100°C), similar to dropropizine (same molecular formula but different molecular structure). Studies have shown that the rate of ENDS aerosol removal from room air was greater than that for tobacco cigarette aerosols, 43,44 and this was attributed to rapid evaporation from the ultrafine liquid ENDS aerosol particles (bimodal distribution at 10 and 30 nm), a process less important for about ∼100 nm and much less volatile particles in secondhand tobacco smoke. 44 Another possible reason for the rapid removal rate of ENDS aerosols is their adsorption to the indoor surfaces, for example, walls, sofas, desktops, and clothes.…”
Section: Discussionmentioning
confidence: 99%
“…First, indoor-generated concentrations are seldom known. These can sometimes be substantial, as in smoking tobacco or marijuana, cooking on gas or electric stoves, burning candles, or simply moving about and resuspending particles [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Secondly, little is known about the times the residents are not at home.…”
Section: Introductionmentioning
confidence: 99%